Unlocking the hidden potential of Mexican teosinte seeds: revealing plant growth-promoting bacterial and fungal biocontrol agents - De-la-Vega-Camarillo, Esaú; Hernández-García, Juan Alfredo; Villa-Tanaca, Lourdes; Hernández-Rodríguez, César (Frontiers in Plant Science, 2023)
The bacterial component of plant holobiont maintains valuable interactions that contribute to plants’ growth, adaptation, stress tolerance, and antagonism to some phytopathogens. Teosinte is the grass plant recognized as the progenitor of modern maize, domesticated by pre-Hispanic civilizations around 9,000 years ago. Three teosinte species are recognized: Zea diploperennis, Zea perennis, and Zea mays. In this work, the bacterial diversity of three species of Mexican teosinte seeds was explored by massive sequencing of 16S rRNA amplicons. Streptomyces, Acinetobacter, Olivibacter, Erwinia, Bacillus, Pseudomonas, Cellvibrio, Achromobacter, Devosia, Lysobacter, Sphingopyxis, Stenotrophomonas, Ochrobactrum, Delftia, Lactobacillus, among others, were the bacterial genera mainly represented. The bacterial alpha diversity in the seeds of Z. diploperennis was the highest, while the alpha diversity in Z. mays subsp. mexicana race was the lowest observed among the species and races. The Mexican teosintes analyzed had a core bacteriome of 38 bacterial genera, including several recognized plant growth promoters or fungal biocontrol agents such as Agrobacterium, Burkholderia, Erwinia, Lactobacillus, Ochrobactrum, Paenibacillus, Pseudomonas, Sphingomonas, Streptomyces, among other. Metabolic inference analysis by PICRUSt2 of bacterial genera showed several pathways related to plant growth promotion (PGP), biological control, and environmental adaptation. The implications of these findings are far-reaching, as they highlight the existence of an exceptional bacterial germplasm reservoir teeming with potential plant growth promotion bacteria (PGPB). This reserve holds the key to cultivating innovative bioinoculants and formidable fungal antagonistic strains, thereby paving the way for a more sustainable and eco-friendly approach to agriculture. Embracing these novel NGS-based techniques and understanding the profound impact of the vertical transference of microorganisms from seeds could revolutionize the future of agriculture and develop a new era of symbiotic harmony between plants and microbes.